The hygiene and motivational factors in relation to job satisfaction of teachers in fifteen public elementary schools of Sagay, Negros Occidental - Tabanao, Susana Cangque (Animo Repository, 1989)
This study analyzes the factors that strongly contribute to the job satisfaction of teachers of the fifteen (15) public elementary schools of Sagay, Negros Occidental. The descriptive correlational method of research was utilized in the study to determine the relationship between the actual extent of provision of hygiene and motivation factors and the level of job satisfaction of teachers, and to determine the factors that contribute to the satisfaction of teachers. The study was confined to the teachers of the fifteen (15) public elementary schools of Sagay, District One in Negros Occidental in the school year 1988-1989. The total number of teachers subjected to the study was two hundred twenty (220). Out of 220, 183 returned the accomplished questionnaires. Two instruments were used to measure the extent to which motivation and hygiene factors were provided by the school/s and the actual level of teachers' job satisfaction. These instruments were: Factors Important in My Job, a validated instrument developed by the Development Academy of the Philippines (DAP) and Job Satisfaction Questionnaire, a validated instrument developed by Miguel (1980). To determine the relationship between the moderator variables like age, sex, civil status, educational attainment and length of teaching service and the relationship between motivation, hygiene and job satisfaction of teachers, correlational analysis was used. To predict the predictors of the teachers' job satisfaction, regression analysis was used. From the results of the study, it was concluded that generally, the respondent-teachers were happy, contented and satisfied with their job despite low salary. The teachers derived satisfaction from both motivation and hygiene factors. There was no clear distinction as to what factors contributed to the job satisfaction of teachers and/or dissatisfaction. The moderator variables: age, sex, civil status, educational attainment and length of teaching service were not related with job satisfaction of teachers. The teachers' job satisfaction can be predicted by the extent of provision of the hygiene and the motivational factors.